SENSORS CONFIGURATION FOR SMALL SCALE AUTONOMOUS GROUND VEHICLE - Aparow, Vimal Rau; Hassan, Muhammad Zahir; Hudha, Khisbullah; Ahmad, Fauzi (2012)
This paper presents a small scale autonomous ground vehicle which is configured using sensors. The autonomous small scaled vehicle engineered to have dynamic behaviors equivalent with real ground vehicle. The main purpose is to use sensors configuration is to scale environment interactively with human operator. Sensors configuration equipped with more electronic instruments, Arduino Duemilanove, wireless communication system, data acquisition system and number of sensors. The simulation and experiment is provided.